Marijuana advertising exposure among current marijuana users in the U.S. (1st May 2017) - Krauss, Melissa J.; Sowles, Shaina J.; Sehi, Auriann; Spitznagel, Edward L.; Berg, Carla J.; Bierut, Laura J.; Cavazos-Rehg, Patricia A.
Highlights: Surveyed 18–34 year old past month marijuana users living in the U.S. (N = 742). Over half of participants were exposed to marijuana advertising in the past month. Advertisements were commonly viewed on digital media (i.e. online, social media). Exposure to marijuana advertising was associated with heavier, more potent use. Abstract: Background: Little is known about marijuana advertising exposure among users in the U.S. We examined the prevalence of advertising exposure among young adult marijuana users through traditional and new media, and identified characteristics associated with seeking advertisements. Methods: We conducted a cross-sectional survey of 18–34 year-old past-month marijuana users in the U.S. using a pre-existing online panel (N = 742). The survey queried about passively viewing and actively seeking marijuana advertisements in the past month, sources of advertisements, and marijuana use characteristics. Results: Over half of participants were exposed to marijuana advertising in the past month (28% passively observed advertisements, 26% actively sought advertisements). Common sources for observing advertisements were digital media (i.e., social media, online, text/emails; 77%). Similarly, those actively seeking advertisements often used Internet search engines (65%) and social media (53%). Seeking advertisements was more common among those who used medically (41% medical only, 36% medical and recreational) than recreational users (18%), who used concentrates or edibles (44% and 43%) compared to those who did not (20% and 19%), and who used multiple times per day (33%) compared to those who did not (19%) (all p < 0.01). Conclusions: Exposure to marijuana advertising among users is common, especially via digital media, and is associated with medical use, heavier use, and use of novel products with higher THC concentrations (i.e., concentrates) or longer intoxication duration (i.e., edibles). As the U.S. marijuana policy landscape changes, it will be important to examine potential causal associations between advertising exposure and continuation or frequency/quantity of use.